O-204 Intensive care unit physicians' challenges on occupational safety and health during the COVID-19 pandemic: a scoping review. (14th March 2023) - Harith, Abdul Aziz; Griffiths, Rob; Myers, Julia; Stubbe, Maria; Tietjens, Donna
Abstract : Introduction: Demand exceeded capacity during COVID 'surges' in certain intensive care units around the world, resulting in avoidable deaths, workload pressures on staff, longer and more intensive care, and an increased risk of staff infection during intensive interventions. A limited number of studies examined intensive care physicians' experiences and perceptions during the COVID-19 pandemic. This review summarises the available published articles related to the challenges faced by ICU consultants during the COVID-19 pandemic from an occupational safety and health perspective. Material and Methods: The PRISMA-ScR guidelines were applied to four online databases, including Medline, Scopus, Web of Science (WOS), and PsycINFO, to identify articles published between January 2020 and October 2022. During the COVID-19 pandemic, ICU consultants' experiences and perspectives on occupational safety and health as a primary outcome are examined. Results: The full texts 61 articles were then considered; 25 articles met the inclusion criteria, which include English language full texts of available articles, qualitative studies, and ICU consultants. Eight main themes emerged from the synthesis: COVID-19 infection, psychosocial distress, moral distress, physical distress, workplace violence, social stigma, structural and organisational issues, and risk communication. Phenomenological studies make up the majority of the qualitative research, followed by grounded theory studies and case studies. Conclusions: The global impact of the COVID-19 pandemic on intensive care services has been catastrophic. The key to maintaining ICU services during a pandemic is preparedness, adaptation, and mitigation. Consequently, it is essential to acknowledge the ICU consultant's perspective in order to mitigate all potential ICU service disruptions. However, anticipating action for a variety of issues or challenges is best explored through a qualitative interpretive description study directed at ICU consultants with on-the-ground experience.